A review of the anti‐inflammatory properties of antidiabetic agents providing protective effects against vascular complications in diabetes. Issue 6 (11th November 2018) - Yaribeygi, Habib; Atkin, Stephen L.; Pirro, Matteo; Sahebkar, Amirhossein
Abstract: The global prevalence of Type 2 diabetes mellitus and its associated complications are growing rapidly. Although the role of hyperglycemia is well recognized in the pathophysiology of diabetic complications, its exact underlying mechanisms are not fully understood. In this regard, accumulating evidence suggests that the role of inflammation appears pivotal, with studies showing that most diabetic complications are associated with an inflammatory response. Several classes of antidiabetic agents have been introduced for controlling glycemia, with evidence that these pharmacological agents may have modulatory effects on inflammation beyond their glucose‐lowering activity. Here we review the latest evidence on the anti‐inflammatory effects of commonly used antidiabetic medications and discuss the relevance of these effects on preventing diabetic complications.